Assessing the diagnostic accuracy of PCR-based detection of Streptococcus pneumoniae from nasopharyngeal swabs collected for viral studies in Canadian adults hospitalised with community-acquired pneumonia: a Serious Outcomes Surveillance (SOS) Network of the Canadian Immunization Research (CIRN) study. Issue 6 (8th June 2017) - Gillis, Hayley D; Lang, Amanda L S; ElSherif, May; Martin, Irene; Hatchette, Todd F; McNeil, Shelly A; LeBlanc, Jason J
Abstract : Study design: Detection and serotyping of Streptococcus pneumoniae are important to assess the impact of pneumococcal vaccines. This study describes the diagnostic accuracy of PCR-based detection of S. pneumoniae directly from nasopharyngeal (NP) swabs collected for respiratory virus studies. Methods: Active surveillance for community-acquired pneumonia (CAP) in hospitalised adults was performed from December 2010 to 2013. Detection of pneumococcal CAP (CAPSpn ) was performed by urine antigen detection (UAD), identification of S. pneumoniae in sputum or blood cultures. S. pneumoniae was detected in NP swabs using lytA and cpsA real-time PCR, and serotyping was performed using conventional and real-time multiplex PCRs. For serotyping, the Quellung reaction, PCR-based serotyping or a serotype-specific UAD was used. Results: NP swab results were compared against CAP cases where all pneumococcal tests were performed (n=434), or where at least one test was performed (n=1616). CAPSpn was identified in 22.1% (96/434) and 14.9% (240/1616), respectively. The sensitivity of NP swab PCR for the detection of S. pneumoniae was poor for CAPSpn (35.4% (34/96) and 34.17% (82/240)), but high specificity was observed (99.4% (336/338) and 97.89% (1347/1376)). Of the positive NP swabs, a serotype could be deduced by PCR in 88.2% (30/34) and 93.9% (77/82), respectively. Conclusions: While further optimisation may be needed to increase the sensitivity of PCR-based detection, its high specificity suggests there is a value for pneumococcal surveillance. With many laboratories archiving specimens for influenza virus surveillance, this specimen type could provide a non-culture-based method for pneumococcal surveillance.